Penguatan Nilai-Nilai Toleransi Dan Multikultural Melalui Huma Lentera Pada Masyarakat Desa Tarusan Danum Kabupaten Katingan - Bayu Kencono; Eka Suriansyah; Kadek Sukiada; Wirastiani Binti Yusup; Rida Alfiana; Enjelina Kristamia; Tamara Tamara; Tan Giok; Prin Andika; Seri Hartati Julianti; Mita Riyani; Lasmini Lasmini; I Ketut Pujo Kartiko; Komang Ayu Anom Swandewi (FKIP, Universitas Palangka Raya, 2023)
Strengthening the values of tolerance and diversity is essential in the life of the nation and state today. Horizontal conflicts based on Ethnicity, Race, Religion, and Class are increasingly influencing the situation. Therefore, it is important to promote genuine tolerance, as seen in Tarusan Danum Village, Katingan District. The purpose of community service there is to strengthen tolerance and diversity which is starting to decline. The method used in this service is PAR (Participation Action Research). The results show that in Tarusan Danum Village, in difficult situations, people help each other regardless of religion. Gotong-royong in cleaning public cemeteries is also carried out regardless of religious differences, because people see all religions as part of God's creation. This mutual help increases harmony between religious communities and promotes moderation and tolerance in religion. This service succeeded in strengthening religious moderation, strengthening tolerance, and building togetherness among people of various religions in Tarusan Danum Village